2022
DOI: 10.1021/acssuschemeng.2c02954
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acidic Ternary Deep Eutectic Solvent Treatment on Native Lignin

Abstract: Ternary deep eutectic solvents (DESs) are gaining increased attention to serve as a cheap green alternative medium for the processing of lignocellulosic biomass. For example, mixtures of choline chloride (ChCl), ethylene glycol (EG), and oxalic acid (OA) were recently explored for the fractionation of lignocellulosic biomass into its main components. Interestingly, during this processing, the recovered lignin was structurally modified by incorporation of EG, which altered its solubility properties and led to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 47 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…This result may be because the main connecting bonds (ether bonds) in the lignin were not destroyed, thus preserving its original structure. Previous studies reported that the addition of ethylene glycol to DES can effectively preserve the β- O -4 bond in lignin and inhibit lignin condensation [ 26 , 27 ]. Moreover, the polydispersity index (PDI) can directly reflect homogeneity in the molecular weight distribution of lignin; when the PDI is lower than 3, lignin is considered to be a homogeneous polymer [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…This result may be because the main connecting bonds (ether bonds) in the lignin were not destroyed, thus preserving its original structure. Previous studies reported that the addition of ethylene glycol to DES can effectively preserve the β- O -4 bond in lignin and inhibit lignin condensation [ 26 , 27 ]. Moreover, the polydispersity index (PDI) can directly reflect homogeneity in the molecular weight distribution of lignin; when the PDI is lower than 3, lignin is considered to be a homogeneous polymer [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…4-Propyl catechol was selectively extracted through the depolymerization of lignin. 153 Wang et al 154 explored a brilliant idea to process 4 different lignocellulosic biomasses (birch, pine, reed, and walnut) with ternary DESs composed of ChCl : EG with OA and HOTf at different reaction conditions. The discussed DESs are in situ capable of incorporating the EG (80-85%), and large linkage content (60-80% aryl ether linkage) into the residual enzymatic lignin.…”
Section: Lignin Processing Using Dessmentioning
confidence: 99%
“…The rich hydrogen bonding and acidity of acid DES swell the structure of corn stover by disrupting the hydrogen bonding between cellulose fibers and dissolving hemicellulose and acid-insoluble lignin. [24][25][26] 2D-HSQC NMR can determine the specific carbon-hydrogen functionalities to identify the structural features of low molecular weight lignin fragments, which can predict the cleavage of bonds. The aromatic region (δ C /δ H 135-95/6.3-8.0) and side-chain region (δ C /δ H 90-50/3.0-5.5) of the HSQC NMR spectra of DES extracted lignin and low-alkali extracted lignin are shown in Figure 2A,B.…”
Section: Characterizationmentioning
confidence: 99%